O lugar é aqui e o tempo é agora: Uma investigação do desenho como registro do cotidiano - Leticia Crespo Grandinetti (2007)
This work has the objective of investigating drawing and its several roles as a day-to-day recording. It also intends to reflect on these possibilities, examining the relationship between art and quotidian.Considered for long as a secondary technique, drawing has been established as an artistic independent possibility, and its potential has been expanded, comprising aspects that were before, considered out of its scope. This means of expression has been a chain between the artist and his subjectivity, through works that deal with emotions, personal experiences and feelings. The research developed here is about the drawing directly involved with the contemporary human being who moves widely into space, who deals with complex issues related to time and who interacts with the environment specially through the eyes.From the theoretical point of view, this work rests on Michel de Certeau`sthoughts which present the invention of quotidian as the result of the art ofdoing. Also, the research relies on Gaston Bachelard who sees space as a possibility of rescuing situations abducted by the time. Jean Baudrillard points out ways of dealing with objects and Roger Chartier ways of dealing with books. Tearing the limits between writing and image, supported here by Michel Foucault, the research contemplates the production of diaries and books of artists, through which the meaning and format implied in the codex idea, can be widened. At this point Roland Barthes, Maurice Blanchot and other writers linked with the notion of book, writing and the production of feelings are also mentioned.